FAKTOR - FAKTOR YANG BERHUBUNGAN DENGAN PENERAPAN KOMUNIKASI SBAR PADA SAAT OVERAN DINAS DI RUANG RAWAT INAP - Fitrianola Rezkiki (HUMAN CARE JOURNAL, 2016)
AbstractThe application of communication SBAR is one effort in improving security hospital patients .Based on the report institute of medicine to err is human building a safer health system in 2012 around 3- 6 % scene not expected ( ktd ) the last extend long day rawatan or inflict disability in hospital patients .Research aims to understand factors that deals with the application of communication SBAR at the time overan government offices in inpatient rooms RSAM Bukittinggi. The kind of research this is descriptive analytic with the approach cross sectional study.Population this research is nurse as the team head of the in inpatient rooms RSAM Bukittinggi.The sample collection using a technique total of sampling as many as 36 people.Date collection use sheets of kuisioner and a observation the implementation of the SBAR.Date analysis covering analysis unviariat and analysis bivariat use chi-square test. Based on the results of research know that 83,3 % of respondents knowledge high, 61,1 % with response negative attitude, 50 % with the motivation low and rp 66.7 % of respondents not to apply communication SBAR appropriate with the SOP.There was a correlation the attitude ( p = 0,003, or = 11.4 ), motivation ( p = 0,013, or = 10 and there was no connection knowledge ( p = 1,000 ) by the application of communication SBARin overan agency. Concluded that attitude and motivation nurse associated with the implementation of the communication SBAR in overan agency  so expected to the team head of the nursing to can always motivate self and the team members nursing to they do care nursing appropriate with the SOP including in the implementation of the communication SBAR at the time overan agency.Keywords         : Knowledge , Attitude , Motivation , Communication SBAR